Inversion for the static friction coefficient of seismogenic faults: Application to induced seismicity of the Basel Enhanced Geothermal System, Switzerland. (May 2021) - Viganò, Alfio; Ranalli, Giorgio; Andreis, Daniele; Martin, Silvana
Highlights: Method of inversion for friction coefficient on seismogenic faults. Application to the Basel Enhanced Geothermal System. Friction coefficient in shallow continental crust compatible with laboratory data. Abstract: The static coefficient of friction describes the strength of faults and is considered to vary in nature between typical laboratory values measured on a large variety of rocks ( 0.6 - 0.85 ) and very low values for fault rocks containing talc, chlorite and kaolinite ( < 0.3 ). The effective frictional strength of a seismically active fault is the result of a combination of frictional properties of the fault rocks and the prevailing pore fluid pressures, which can reach supra-hydrostatic values permitting unfavourably oriented faults to slip. Here, we present an iterative inversion procedure to obtain the average static friction coefficient of a population of seismic faults, provided that stress tensor, geometry of faults and fluid pressures are adequately constrained. The application to a dataset of 48 seismically activated faults (earthquake moment magnitude, MW ≤ 3.0 ) by fluid injection in crystalline basement in the Basel Enhanced Geothermal System (Switzerland) yields an average coefficient of friction of 0.66 ± 0.11 . The inversion results, which are well constrained by high-quality focal mechanisms and robust above-hydrostatic fluid pressure estimations, have uncertainty primarily dependent on the principal stress and fault plane orientations. Values of the friction coefficient in crystalline rocks in the continental basement are compatible with experimentally determined values but require supra-hydrostatic fluid pressures. A comprehensive characterization of all the frictional parameters should be required to better assess rheological and stability fault models, both for natural and human induced earthquakes.